Orchidaceae in Santa Catarina: Update, geographic distribution and conservation - Carlos Siqueira; Ana Zanin; Luiz Neto (Check List, 2014)
This study consists of a checklist and an analysis of the spatial distribution of the species of Orchidaceae of the Brazilian state of Santa Catarina. Based on literature, the accepted names and current synonyms for the species in the state are cited. The occurrence of 121 genera and 560 accepted species was detected, 12 of them endemic. Of the three subfamilies represented in the state, Epidendroideae is the most representative, with 94 genera and 432 species, followed by Orchidoideae with 25 genera and 122 species, and Vanilloideae, with only two genera and six species. According to the criteria of the International Union for Conservation of Nature, 24 species fall within the vulnerable category, seven are endangered and four are critically endangered. The life form, plant formation and habitat of each species are also presented.